The Idea of Political Representation and Its Paradoxes - Waśkiewicz, Andrzej (2020)
If we want to understand the vicissitudes of modern democracy then, argues the author, we need to analyse the ideas upon which representative government is based rather than compare contemporary conditions with the Greek ideal. These principal ideas have been presented clearly in past centuries, when the relation between democracy and representation was still a matter of political judgement. The old masters of political thinking clarified the functions of representation: legitimising power, creating sovereignty but also setting its limits, and pursuing the common good while still reflecting social diversity. Because institutions of representation are expected to fulfil a variety of functions, these institutions have in recent times come under attack for standing in the way of radical programs for democratising democracy. The author of this book reminds us that these functions are necessary in every political order, whether democratic or not. Instead of rejecting representation, political theorists should focus on making government more accountable.